THE ROLE AND CHALLENGES OF ISLAMIC EDUCATION IN INDONESIA IN THE DISRUPTIVE ERA: THE ANALYSIS OF THE SYSTEM OF ISLAMIC EDUCATION CHARACTER IN INDONESIA - Imam Syafi'i; Syaifulloh Yusuf (Akademika : Jurnal Pemikiran Islam, 2021)
Various types of character education theories have swiftly developed, such as Thomas Lickona's notion of moral knowing, moral emotion, and moral deeds. The Presidential Regulation No. 87 of 2017 on Strengthening of Character Education has also spawned a slew of derivative theories. Some of the new results in character education are holistic-integrative and character-interconnected. However, character education, particularly Islamic education, continues to be a source of concern for all parties. The challenges of Islamic education are increasing with the sophistication of technology. The community's faltering use of technology is a major impediment to increasing Islamic education's principles. This study's research technique is descriptive-qualitative, utilizing literature reviews from a variety of scientific data sources. According to the findings and conclusions of this study, Islamic education in Indonesia plays both a function and a challenge in the age of disruption. Problems in the sphere of educational technology, the dichotomy of science, educational evaluation, subject matter delivery, and geographical challenges of Islamic education are among the challenges in Islamic education. Thus, to create a golden generation of Indonesia in 2045, Islamic education plays an important role in maintaining Islamic values, character values and noble character.